2011
DOI: 10.1007/s00417-011-1751-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of matrine on proliferation and apoptosis of cultured retinoblastoma cells

Abstract: Matrine added to cultures of immortalized retinoblastoma cells led to a reduced tumor cell proliferation, decreased rate of mitosis and an increased tumor cell apoptosis, paralleled by corresponding changes in the proteins regulating the cell cycle or apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…Matrine, a component rich in SF, inhibited cell proliferation through arresting cells in G0/G1 phase in gallbladder cancer cells (31), prostate cancer cells (32) and hepatoma cells (33). Qin et al and Zhao et al reported that matrine downregulated the expression of cyclin D1 to inhibit the growth of retinoblastoma cells (34,35). The results of the present study with EE-JXY are consistent with these reports, although the underlying mechanism is unknown.…”
Section: Discussionsupporting
confidence: 90%
“…Matrine, a component rich in SF, inhibited cell proliferation through arresting cells in G0/G1 phase in gallbladder cancer cells (31), prostate cancer cells (32) and hepatoma cells (33). Qin et al and Zhao et al reported that matrine downregulated the expression of cyclin D1 to inhibit the growth of retinoblastoma cells (34,35). The results of the present study with EE-JXY are consistent with these reports, although the underlying mechanism is unknown.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies showed that MT dose-dependently inhibited the proliferation of human retinoblastoma cells (Y79, WERI-RB1, and SO-RB50), and induced cell cycle arrest at the G0/G1 phase in a time-dependent manner. The intracellular mechanisms involved are related to increased levels of the CDK inhibitors p21 and p27, and the decreased levels of the cyclin D1 protein ( Zhao et al., 2012 ). Melanoma M21 cells also showed similar effects ( Jin et al., 2013 ).…”
Section: Pharmacologymentioning
confidence: 99%
“…In a rat hepatic stellate cell line (HSC-T6), it was reported that a combination of MT and glycyrrhizin (100 µM MT+glycyrrhizin) inhibited proliferation of activated HSCs and reduced levels of collagen I and hexadecenoic acid (HA). It was also found that combination of MT and glycyrrhizin, 1 mg/mL MT and 1 mg/mL glycyrrhizin, given at a dose of 0.1 mL/100g body weight significantly reduced serum laminin (LN), HA and procollagen type-III (PC-III) levels in a rat model of CCl 4 -induced liver fibrosis, when compared with MT or glycyrrhizin alone ( Zhao et al., 2012 ). Administration of a mixture of 1 mg/mL glycyrrhizin and 1 mg/mL MT to mice at a dose of 0.5 mL/20g body weight decreased mortality of acetaminophen-overdosed mice, reduced acetaminophen-induced hepatotoxicity, and decreased the area and number of glutamyl transpeptidase (-GT)+positive foci, thereby restoring liver function and preventing liver cancer ( Wan et al., 2009 ).…”
Section: Drug-drug Interactions Of Mtmentioning
confidence: 99%
“…At present, OMT has been widely used in the treatment of hepatitis B and liver fibrosis in China (2). Furthermore, OMT may exert its anticancer activities through various channels, primarily by inhibiting cancer cell proliferation (3), inducing cell cycle arrest (4) and differentiation (5), accelerating apoptosis (6), restraining agiogenesis (7), inhibiting metastasis and invasion (8), and preventing or reducing chemotherapy- and radiotherapy-induced toxicities (9). However, these previous studies are mostly limited to observations of superficial phenomenon and lack systematic investigation using modern molecular biology techniques.…”
Section: Introductionmentioning
confidence: 99%